2018
DOI: 10.1002/14651858.cd010638.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral and sublingual immunotherapy for egg allergy

Abstract: Editorial group: Cochrane Tobacco Addiction Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 4, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 48 publications
1
73
0
5
Order By: Relevance
“…OIT has been demonstrated to be an effective treatment option to induce desensitization in patients with food allergy . Previous randomized controlled studies using home‐based protocols with various increment rates have reported lower total desensitization rates: Staden et al reached 2.8 g protein of lyophilized hen's egg powder in 7 of 11 (48%) patients in a mean induction period of 7 months; Moriset et al reached only 7 g of raw egg white (0.77 g proteins) after 6 months of treatment in 69.4% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OIT has been demonstrated to be an effective treatment option to induce desensitization in patients with food allergy . Previous randomized controlled studies using home‐based protocols with various increment rates have reported lower total desensitization rates: Staden et al reached 2.8 g protein of lyophilized hen's egg powder in 7 of 11 (48%) patients in a mean induction period of 7 months; Moriset et al reached only 7 g of raw egg white (0.77 g proteins) after 6 months of treatment in 69.4% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oral immunotherapy (OIT) has been shown to be an effective treatment to induce desensitization in patients with egg allergy . However, OIT is a long‐term treatment with associated dose adverse reactions (DARs), which are typically related to the buildup desensitization phase, requiring close medical monitoring. Rush OIT protocols are shorter, but they have been associated with more frequent and severe DARs than slower protocols .…”
Section: Introductionmentioning
confidence: 99%
“…The methodological quality of RCTs was assessed according to the Cochrane risk of bias approach [21], using published risk of bias assessments from systematic reviews, whenever available [22][23][24]. For case series, the Institute of Health Economics Quality Appraisal of Case Series Studies Checklist was applied [25].…”
Section: Selection Of Clinical Studies and Assessment Of Their Methodmentioning
confidence: 99%
“…There is no convincing evidence of a clinically significant difference between food allergens in terms of safety and efficacy outcomes in OIT for the treatment of IgEmediated food allergy. Therefore, all recommendations in these CPGs are generally applicable to all food allergens, unless there is specific evidence to demonstrate otherwise This recommendation is based on the principle of equity of eligibility It is supported by large amount of consistent clinical evidence, considering the absence of demonstrated lack of efficacy or of a consistent safety issue for any specific food despite a large number of clinical studies for a variety of foods [22][23][24][29][30][31][32][33][34][35][36][37][38]. Level of evidence: HIGH It is also supported by the lack of biological plausibility that the mechanism of OIT would differ from one allergen to another.…”
Section: Ethical Imperative Data or Other Considerations In Support mentioning
confidence: 99%
“…However, some children have persistent egg allergy (Savage, Matsui, Skripak, & Wood, 2007), which could be life threatening (Macdougall, Cant, & Colver, 2002). To date, no effective method has been developed to manage egg allergy, and the best way for egg‐allergic people is to avoid eggs and egg‐containing foods strictly (Romantsik, Tosca, Zappettini, & Calevo, 2018). …”
Section: Introductionmentioning
confidence: 99%